Effect of Pulsed Jet on Pore Pressure of Deep Formation Rock. (29th December 2021) - Wang, Yong; Ni, Hongjian; Wang, Ruihe; Lei, Peng; Huang, Bin; Liu, Shubin; Li, Ning
Abstract : Pulsed jet significantly affects the pore pressure of deep formation and then affects the mechanical ROP. In this paper, the effect of jet pulsation on deep pore pressure in the formation is studied by the finite element method. Under the pulsed jet, the maximum relative negative pressure is along the wellbore axis, and the farther it is to the borehole axis, the smaller the relative negative pressure is. With the increase of pulse frequency, the relative negative pressure increases and the maximum point of relative negative pressure moves upward. The optimum pulse frequency is from 50 Hz to 500 Hz. There is a linear relationship between pulse amplitude and relative negative pressure.